(untitled) (Research, Society and Development, 2022)
The analysis of fucoxanthin (FCX) in algal biomasses presents some limitations, especially regarding the sample preservation after collection until extraction of the pigment. FCX stability was evaluated in biomass samples of one diatom and three brown seaweed species (Phaeophyceae) and their extracts stored at -20ºC and -80ºC, for 60 days. Fucoxanthin was quantified through UHPLC-DAD. The methanolic extracts of the micro/macroalga biomasses stored at -20ºC and -80ºC were more effective in preserving the xanthophyll, comparatively to the algal biomasses. Besides, the chromatographic analysis showed an increase in the FCX’s peak retention time along the sample storage, possibly due to the trans→cis isomerization of the molecule. Such information is relevant for choosing the best protocol for storing and preserving at most FCX, because changes in the geometric conformations of the molecule over storage strongly affects its biological activities.